Fenomena Phubbing Remaja Kota Surabaya dan Jakarta - Lutfiana, Nita; Arviani, Heidy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to find out about the facts, causes and impacts of the phubbing phenomenon on adolescents in the cities of Surabaya and Jakarta. This type of research used a qualitative research method with a phenomenological study. The data needed in this study is qualitative data as primary data in the form of images, words and not numbers in a discourse about the phenomenon of phubbing as a degradation of social relations as a result of social media. Based on the results of the study, it was found that 1) Teenagers in the cities of Surabaya and Jakarta have a fairly high intensity of using cellphones with a number of more than 5 hours per day which on average starts when they are students in elementary school; 2) The phenomenon of phubbing carried out by teenagers in the cities of Surabaya and Jakarta is caused by excessive anxiety that information on smartphones will be missed so that they check regularly. In addition, they are also sometimes not aware of their phubbing behavior because they focus on smartphones whether they are used to play games or play social media; 3) The bad impact they receive when doing phubbing activities is reducing the quality of face-to-face communication and also disrupting some of the effectiveness of the activities they are doing.